Is There a Role of Autophagy in Depression and Antidepressant Action? - Gassen, Nils C.; Rein, Theo (Frontiers in Psychiatry, 2019)
Autophagy has been recognized as evolutionary conserved intracellular pathway that ensures energy, organelle and protein homeostasis through lysosomal degradation of damaged macromolecules and organelles. It is activated under various stress situations, e.g. food deprivation or proteotoxic conditions. Autophagy has been linked to several diseases, more recently also including stress-related diseases such as depression. A growing number of publications report on the role of autophagy in neurons, also referred to as “neuronal autophagy” on the one hand, and several studies describe effects of antidepressants - or of compounds that exert antidepressant-like actions - on autophagy on the other hand. This minireview highlights the emerging evidence for the involvement of autophagy in the pathology and treatment of depression and discusses current limitations as well as potential avenues for future research.